Expert system for shipboard power plant fault diagnostics and control - Pang, Tow Min. (2009)
The correct diagnosis of faults occurring on ships is a difficult process requiring a large amount of knowledge of shipboard engineering system as well as a broad base of repair experience. The Shipboard Fault Diagnostic Expert System (SFDES) is a prototype of an interactive system that supports the diagnosis of problems in large, slow speed Burmeister and Wain marine diesel engines. This dissertation shows that it is feasible for a computerised system using an expert system to be developed to provide ship's engineering presonnel with the knowledge and experience needed to successfully diagnose faults and take remedial actions.